The Role of Nonapoptotic Programmed Cell Death — Ferroptosis, Necroptosis, and Pyroptosis — in Pancreatic Ductal Adenocarcinoma Treatment - Hsu, Sheng-Kai; Chu, Yi-Hsuan; Syue, Wun-Jyun; Lin, Hugo You-Hsien; Chang, Wen-Tsan; Chen, Jeff Yi-Fu; Wu, Chang-Yi; Yen, Chia-Hung; Cheng, Kai-Chun; Chiu, Chien-Chih (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is the most lethal cancer, with a dismal 5-year survival rate of less than 10%. It is estimated that approximately 80% of pancreatic ductal carcinoma (PDAC) patients are diagnosed at an advanced or metastatic stage. Hence, most patients are not appropriate candidates for surgical resection and therefore require systemic chemotherapy. However, it has been reported that most patients develop chemoresistance within several months, partly because of antiapoptotic mechanisms. Hence, inducing alternative programmed cell death (PCD), including ferroptosis, necroptosis or pyroptosis, seems to be a promising strategy to overcome antiapoptosis-mediated chemoresistance. In this review, we shed light on the molecular mechanisms of ferroptosis, necroptosis and pyroptosis and suggest several potential strategies (e.g., compounds and nanoparticles [NPs]) that are capable of triggering nonapoptotic PCD to suppress PDAC progression. In conclusion, these strategies might serve as adjuvants in combination with clinical first-line chemotherapies to improve patient survival rates.